The impact of China's 1989 Tiananmen massacre - Béja, Jean-Philippe (China policy series ;, 2011)
The 1989 pro-democracy movement in China constituted a huge challenge to the survival of the Chinese communist regime. This book assesses the impact of the movement, and of the ensuing repression on the political evolution of the People's Republic of C.